Identification of sites in apolipoprotein A-I susceptible to chymase and carboxypeptidase A digestion. Issue 1 (6th December 2012) - Usami, Yoko; Kobayashi, Yukihiro; Kameda, Takahiro; Miyazaki, Akari; Matsuda, Kazuyuki; Sugano, Mitsutoshi; Kawasaki, Kenji; Kurihara, Yuriko; Kasama, Takeshi; Tozuka, Minoru
Abstract : MCs (mast cells) adversely affect atherosclerosis by promoting the progression of lesions and plaque destabilization. MC chymase cleaves apoA-I (apolipoprotein A-I), the main protein component of HDL (high-density lipoprotein). We previously showed that C-terminally truncated apoA-I (cleaved at the carboxyl side of Phe 225 ) is present in normal human serum using a newly developed specific mAb (monoclonal antibody). In the present study, we aimed to identify chymase-induced cleavage sites in both lipid-free and lipid-bound (HDL3 ) forms of apoA-I. Lipid-free apoA-I was preferentially digested by chymase, at the C-terminus rather than the N-terminus. Phe 229 and Tyr 192 residues were the main cleavage sites. Interestingly, the Phe 225 residue was a minor cleavage site. In contrast, the same concentration of chymase failed to digest apoA-I in HDL3 ; however, a 100-fold higher concentration of chymase modestly digested apoA-I in HDL3 at only the N-terminus, especially at Phe 33 . CPA (carboxypeptidase A) is another MC protease, co-localized with chymase in severe atherosclerotic lesions. CPA, in vitro, further cleaved C-terminal Phe 225 and Phe 229 residues newly exposed by chymase, but did not cleave Tyr 192 . These results indicate that several forms of C-terminally and N-terminally truncated apoA-I could exist in the circulation. They may be useful as new biomarkers to assess the risk of CVD (cardiovascular disease).